Video Drama Intervention on Knowledge of Breast Cancer and Practice Intention of its Early Detection Methods - Adekoya, Helen Odunola; Chinanu-Akpuh, Chinwe Comfort (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
The rising incidences of breast cancer, high mortality and morbidity rates, and poor knowledgeability level of the disease and low practice intentions of its early detection methods among rural women is constituting serious health challenge in Nigeria. These conditions are often blamed on inadequate infrastructures and poor enlightenment avenues. Consequently, these observed situations demand for planned education in favour of the rural women. Therefore, the study examined the effects of video drama intervention on the knowledge of breast cancer and practice intention of its early detection methods among Aboh Mbaise women of Imo State, Nigeria. A quasi-experiment was conducted on 100 women; (Amaasa, experiment and Ngwuru-Nweke, control). The Aboh-Mbaise women at reproductive age constituted the population of the study. The participants were recruited using simple random sampling by balloting. Data was retrieved using validated questionnaire at pre-test and post-test evaluation with reliability confidence of 0.799. Health belief model and attitude change theory underpinned the study. Data was analysed using paired sampled t-test. The findings showed that the intervention significantly improved participants’ knowledge of; breast cancer ( x̅ =42.02 experimental and x̅ =26.02 control), early detection methods ( t (49)=22.74, p =0.000<0.05) and intention to practice the methods ( t (49)=19.50, p =0.000<0.05), with a significant difference of ( t (49)=1.95, p =0.057>0.05). It was concluded that frequent exposure to health based video drama is effective means of enlightening the rural women on breast cancer concerns, while recommending it application on regularly basis. Keywords: Breast Cancer, Early Detection Methods, Practice Intention, Video Drama Intervention.